Kognitywna interpretacja najnowszych złożeń z powtarzalnym w serii wyrazów członem związanym (na przykładach z języka polskiego i bułgarskiego) - Natalia Długosz (Slavia Meridionalis, 2015)
Cognitive interpretation of newest compounds with a bound component repetitive in a series of words (on the examples from Polish and Bulgarian languages)